Doing science: how to get credit for your scientific work. - Caudri, D (2015)
Everyone deserves to be acknowledged for their efforts and contributions to a shared goal, and getting credit for your scientific work should be part of a natural process and should be fair and straightforward. However, credit cannot be objectively measured despite it having a big influence and, unfortunately, getting appropriate credit can occasionally be both complicated and challenging.